ACTING CLASSES AND EDUCATION: (re)thinking practices and conceptions (Revista Contexto & Educação, 2022)
This article presents a discussion about the teaching of acting in basic education. Through the extension project developed on IFC – Campus Sao Francisco do Sul experiences analysis, we aim to address the acting classes potentialities and challenges. Therefore, we use the project participants interviews, as well  as teachers and artists dedicated to education.
Keywords: Acting. Education. New teaching practices.